Controlled polymerization of methylmethacrylate from fumed SiO2 nanoparticles through atom transfer radical polymerization. Issue 3 (9th May 2013) - Zhang, Juan; Jiang, Long; Pan, Kai; Yi, Zheng; Dan, Yi
Abstract Atom transfer radical polymerization (ATRP) is a promising method to synthesize well‐defined polymer/inorganic nanoparticles. However, the surface‐initiated ATRP from commercially mass produced inorganic nanoparticles has seldom been studied. In this study, the surface‐initiated ATRP of methylmethacrylate (MMA) from commercially mass produced fumed silica (SiO2) nanoparticles was investigated. Unlike the ATRP of MMA initiated from a free initiator, the controllability of ATRP of MMA from the surface of fumed silica nanoparticles was much better using ligand 2, 2'‐bipyridine (bpy) than N, N, N′, N′′, N′′‐pentamethyldiethylenetriamine (PMDETA) as the initiator was immobilized on the surface of the SiO2 nanoparticles and the presence of the SiO2 nanoparticles made the CuCl/bpy catalyst system a homogeneous catalyst system and CuCl/PMDETA a heterogeneous one. The appropriate molar ratio of monomer and initiator was essential for preparing controlled PMMA/SiO2 nanoparticles. The entire process of ATRP of MMA from the surface of SiO2 nanoparticles was controllable when using bpy as ligand, xylene as solvent and with a monomer to initiator ratio of 300:1. The 1H NMR results indicated that the PMMA on the surface of the SiO2 was prepared via ATRP initiated from 4‐(chloromethyl)phenyltrimethoxysilane. The well‐defined PMMA/SiO2 nanoparticles obtained have good thermal stability and are well dispersed in organic media as proved by TGA, dynamic light scattering and transmission electron microscopy. © 2013 Society of Chemical Industry